Azorean bryophyte communities - A revision of differential species. - Sjögren, Erik (2003)
Bryophyte alliances and associations of the nine Azorean islands have been described by the author in publications extending from 1978 to 1997. The present paper includes a revision of their differential species and their differential values. Alliances treated with suggestions of their associations (differential species of the alliances and associations in the relevé tables): Echinodion prolixi Sjn. 93 (epiphytic; mostly above 600 m in native cloud-zone forest types); Lepidozion azoricae Sjn 96 (epixylic; presence as the Echinodion prolixi); Aphanolejeuneo-Colurion Sjn. 78 (epiphyllous; presence as the Echinodion prolixi); Andoae-Nardion scalaris Sjn. 95 (epigeic; from ± 200-1000 m a.s.l.) Ptychomitrion azorici Sjn. 93 (epilithic; in strongly exposed habitats, in coast-near localities to altitudes above 1000 m.; Heterocladio-Jubulion Sjn. 95 (epilithic; in weakly exposed habitats, from about 300 to 800 m a.s.l.). It has benn stressed that differential species occur with different values, both at various altitudes on the individual islands and also with generally reduced values from E to W in the archipelago, due to climatic differences. Only few differential species are restricted to one bryophyte alliance. Also, few bryophyte species are restricted in their presence to one type of substrate. Some of the bryophytes treated are more or less severely threatened as to their survival. Several of these species are differential species of alliances or associations, which mainly occur in mature native forests at altitudes above 500 m. During the last century these forests have become progressively reduced and are now restricted to some of the Azorean islands. Their preservation is highly important and urgent, not only as endemic ancient forest types but also due to their constitution with a large number of endemic vascular plants and bryophytes. LIFE-projects in 1995-1997 have given considerable support to this statement.